The effect of secukinumab treatment on hematological parameters in ankylosing spondylitis and psoriatic arthritis - Karatas, Ahmet; Gercek, Aybuke Nisa; Oz, Burak; Gozel, Nevzat; Sagir, Rabia Piskin; Gur, Mustafa; Koca, Suleyman Serdar (Aves, 2020)
Objective: Secukinumab, a new treatment agent, selectively neutralizes interleukin (IL)-17A. It is used in the treatment of ankylosing spondylitis (AS), psoriatic arthritis (PsA), and psoriasis. It is known that the agents used in the treatment of rheumatic diseases have effects on hematological parameters. In this study, we aimed to determine whether hematological parameters are affected in secukinumab therapy in patients with AS and PsA. Methods: Thirty-six patients on secukinumab treatment were included in the study by scanning the database of our hospital. Data on patients'age, gender, complete blood count (CBC), erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), uric acid, aspartate aminotransferase (AST), alanine aminotransferase (ALT), urea, creatinine values, and additional drug treatments were recorded from our database. The 0- and 6-month values of patients were analyzed. Results: Sixteen males (44.4%) and 20 females (55.6%) were included in our study. The average age was calculated to be 39.8 +/- 8.9 years. Of these, 30 patients receiving secukinumab treatment were diagnosed with AS, and 6 patients were diagnosed with PsA. Twenty-three patients (63.9%) were continued with secukinumab treatment at the 6th month. When CBC, glucose, urea, creatine, AST, ALT, ESR, CRP, and uric acid values of the patients at 0 and 6 months were compared, there was no significant difference. Conclusion: In our study, no significant difference was found between 0 and 6 months in terms of CBC, AST, ALT, urea, creatinine, uric acid, glucose, CRP, and ESR levels in patients receiving secukinumab. However, an increase in hemoglobin values was observed in patients who continued the treatment. These results may suggest that secukinumab treatment has no negative effects on hematological parameters.
Keywords: Secukinumab; ankylosing spondylitis; psoriatic arthritis; hematological parameters